The influence of physical environment on emotion, satisfaction and behavioral intention of patients treated - Hendelyyn, Alvin; Bernarto, Innocentius (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
The purpose of this study is to analyze and examine the influence of physical environment on emotion, satisfaction and behavioral intention of patients treated in Siloam Hospital Lippo Village. This study was conducted using a quantitative approach and an explanatory method. This study involved 100 inpatients treated in Siloam Hospital Lippo Village. The data was collected by using questionnaire processed with PLS-SEM using SmartPLS software. The results showed that physical environment has a direct positive influence on emotion and satisfaction, but does not have a direct influence on behavioral intention of patients treated in Siloam Hospital Lippo Village. This study suggests Siloam Hospital Lippo Village to keep paying attention on the physical environment of the hospital as it can affect the patientâ€™s emotions, satisfaction and behavioral intention.Â Â